State and sub-state nationalism in Southeast Asia - Bertrand, Jacques 1965- (Cambridge University Press, 2024)
Nationalism is a political phenomenon with deep roots in Southeast Asia. Yet, state attempts to create homogenous nations met with resistance. This Element focuses on understanding the rise and subsequent ebbing of sub-state nationalist mobilization in response to state nationalism. Two factors allowed sub-state nationalist movements to be formed and persist: first, state nationalisms that were insufficiently inclusive; second, the state's use of authoritarian tools to implement its nationalist agenda. But Southeast Asian states were able to reduce sub-state nationalist mobilization when they changed their policies to meet two conditions: i) some degree of explicit recognition of the distinctiveness of groups; ii) institutional flexibility toward regional/local territorial units to accommodate a high degree of group self-governance. The Element focuses on four states in the region - namely Indonesia, the Philippines, Thailand, and Myanmar
Title from publisher's bibliographic system (viewed on 05 Dec 2024)
Keywords: Nationalism / Southeast Asia; Southeast Asia / Politics and government